El Archivo de Acción Católica Española (A.C.E.) en la Universidad Pontificia de Salamanca - Caballo, Ana Isabel Huete (Cauriensia, 2022)
The Pontifical University of Salamanca Archives keep and preserve historical records from medieval times. The Spanish Catholic Action Archives represent a great part of the documents kept in the University Archives and are a main source at an international level for the study of 20th Century Spanish Society. This article highlights the great richness of the Spanish Catholic Action archival collections and shows the big chances they have for the research. The archival treatment carried out on the documents eases their consultation by the researchers and general users, and with it we contribute to disseminating the documentary richness of a heritage legacy preserved in Salamanca, collaborating also in this way with the transfer of knowledge and the approaching of documents to the general public.